Interactions of neosaxitoxin with the sodium channel of the frog skeletal muscle fiber (The Rockefeller University Press, 1991)
Neosaxitoxin (neoSTX) differs structurally from saxitoxin (STX) in that the hydrogen on N-1 is replaced by a hydroxyl group. On single frog skeletal muscle fibers in the vaseline-gap voltage clamp, the concentrations for reducing the maximum sodium current by 50% (ED50) at pH's 6.50, 7.25, and 8.25 are, respectively, 4.9, 5.1, and 8.9 nM for STX and 1.6, 2.7, and 17.2 nM for neoSTX. The relative potencies of STX at the different pH's closely parallel the relative abundance of the protonated form of the 7,8,9 guanidinium function, but the relative potencies of neoSTX at the same pH's vary with the relative abundance of the deprotonated N-1 group. In constant-ratio mixtures of the two toxins, the observed ED50's are consistent with the notion that the two toxins compete for the same site. At pH's 6.50 and 7.25, the best agreement between observed and computed values is obtained when the efficacy term (epsilon) for either toxin is 1. At pH 8.25 the best agreement is obtained if the efficacy is 1 for STX but 0.75 for neo- STX. The marked pH dependence of the actions of neoSTX probably reflects the presence of a site in the receptor that interacts with the N-1 -OH, in addition to those interacting with the 7,8,9 guanidinium and the C-12 hydroxyl groups. Considering the three-dimensional structure of the STX and neoSTX molecules, the various site points are probably located in a fold or a crevice of the channel protein, where the extracellular orifice of the sodium channel is located.